Why Don’t You Play the Game? Evaluating the Use of Gamification in an Undergraduate Finance Course - Sevidal, Alfonso Miguel N (Archīum Ateneo, 2021)
The board game Monopoly is used as a gamification tool in an undergraduate finance course in a private business school in the Philippines. The use of Monopoly as a gamification tool is evaluated using Han’s (2015) adaptation of the spiral curriculum and Landers's (2015) theory of gamified learning. According to Han, the spiral curriculum “is the circular model best suited to gamification as pedagogy because it allows students to learn and practice basic skills in order to master advanced tasks.” Meanwhile, Landers’s theory of gamified learning posits that “gamification affects learning via moderation when an instructional designer intends to encourage a behavior or attitude that will increase learning outcomes.” In the undergraduate finance course, the Monopoly board game is used as (i) a means to teach basic principles of financial statement analysis and financial forecasting, consistent with the spiral curriculum and (ii) a moderating tool to help influence key attitudes brought about by prior experiences and preconceived notions on the subject, consistent with Landers’s theory of gamified learning. Findings obtained via a qualitative explanatory approach from 101 undergraduate business students suggest that the use of the Monopoly board game is effective as a gamification tool, as seen in students’ ability to proceed to more advanced topics in the finance course and new opinions on finance as expressed at the end of the course. Recommendations for future study include using a control group, conducting studies at the beginning and end of the course, applying quantitative methods, and addressing exogenous factors that may affect the results.